THE GENERIC LANGUAGE IN THE FUNCTION OF THE RECIPIENT LANGUAGE IN GERMAN (Web of Teachers: Inderscience Research, 2025)
To study the general linguistic essence of a generic language, it is important to pay attention to such a poorly studied area as its contact with other languages (primarily non-native ones). Given the sufficient depth of information currently available on the generic characteristics of German, French, etc. of the generic languages, consideration of the processes of mastering the genus by foreign (non-generic) vocabulary in the recipient generic language is intended to show the stability of its generic subsystem.